Analisis Collaborative Governance dalam Pengelolaan Sampah di Kecamatan Sungailiat Kabupaten Bangka - Andi Ariansyah; Darol Arkum; Sena Putra Prabujaya (Universitas Medan Area, 2026)
The problem of waste management in Sungailiat District, Bangka Regency, shows high complexity along with the increase in waste generation, limited infrastructure, and the lack of optimal institutional capacity and community participation. The management pattern, which is still dominated by a collect-transport-throw approach, emphasizes the need for a paradigm shift towards more collaborative governance. This study aims to analyze collaborative governance practices in waste management in Sungailiat District using a qualitative approach and case study design. Data was collected through in-depth interviews, field observations, and documentation studies, then analyzed using the Collaborative Governance Regime (CGR) framework which includes the context of the system, collaborative dynamics, collaborative capacity, and shared actions and results. The results of the study show that collaboration between actors has emerged, but it is still partial, ad hoc, and has not been strongly institutionalized. Low trust, mutual commitment, and limited capacity of non-governmental actors are the main inhibiting factors. This study concludes that strengthening collaborative governance that is more structured, inclusive, and long-term oriented is needed to realize sustainable waste management at the sub-district level.